Advances and Challenges in Cell-Free Incorporation of Unnatural Amino Acids Into Proteins - Gao, Wei; Cho, Eunhee; Liu, Yingying; Lu, Yuan (Frontiers in Pharmacology, 2019)
Incorporation of unnatural amino acids (UNAAs) into proteins currently is an active biological research area for various fundamental and applied science. In this context, cell-free synthetic biology (CFSB) has been developed and recognized as a robust testing and biomanufacturing platform for highly efficient UNAA incorporation. It enables the orchestration of unnatural biological machinery toward an exclusive user-defined objective of unnatural protein synthesis. This review aims to overview the principles of cell-free unnatural protein synthesis (CFUPS) systems, their advantages, different UNAA incorporation approaches, and recent achievements. These have catalyzed cutting-edge research and diverse emerging applications. Especially, present challenges and future trends are focused and discussed. With the development of CFSB and the fusion with other advanced next-generation technologies, CFUPS systems would explicitly deliver their values for biopharmaceutical applications.